1995
DOI: 10.1016/s1010-7940(05)80161-7
|View full text |Cite
|
Sign up to set email alerts
|

Circulating endothelin in patients undergoing coronary artery bypass grafting

Abstract: Increased synthesis of endothelin, (a powerful physiological vasoconstrictor), is a uniform response to endothelial injury and has been associated with myocardial ischemia and reperfusion. This study tests the hypothesis that coronary artery bypass grafting (CABG) affects endothelin plasma concentrations in various vascular beds. Twenty-four CABG patients were included in this study. Endothelin was determined in multiple plasma specimens obtained from superior vena cava, aortic root and coronary sinus (CS). Ve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
24
0

Year Published

1998
1998
2012
2012

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(25 citation statements)
references
References 25 publications
1
24
0
Order By: Relevance
“…ET levels are elevated in a number of cardiovascular disorders including following myocardial infarction, heart failure and following cardioplegic arrest and cardiac surgery [7][8][9][10][11][12]. It has been suggested that elevated ET-1 levels following ischaemia may result in the so called ' low coronary reflow ' phenomenon [13].…”
Section: Introductionmentioning
confidence: 99%
“…ET levels are elevated in a number of cardiovascular disorders including following myocardial infarction, heart failure and following cardioplegic arrest and cardiac surgery [7][8][9][10][11][12]. It has been suggested that elevated ET-1 levels following ischaemia may result in the so called ' low coronary reflow ' phenomenon [13].…”
Section: Introductionmentioning
confidence: 99%
“…It is documented that ET-1 might affect postoperative outcome negatively in patients undergoing cardiac surgery [8,9,18]. Previous studies have reported that during cardiac surgery, the use of CPB leads to elevated plasma levels of ET-1 [19,20], and that levels remain elevated for 24 h [8,18]. Zhu et al [21] demonstrated that plasma ET-1 peaked after cessation of CPB in patients undergoing valvular surgery and correlated positively with bypass time.…”
Section: Discussionmentioning
confidence: 99%
“…ET levels are elevated in a number of cardiovascular disorders, including following myocardial infarction, heart failure and following cardioplegic arrest and cardiac surgery [4][5][6][7][8][9]. This may appear surprising in the absence of the up-regulation of preproET-1 mRNA expression.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have also demonstrated the role of ET-1 in basal coronary tone in rats [2] and humans [3]. ET levels are elevated in a number of cardiovascular disorders, including following myocardial infarction, heart failure and following cardioplegic arrest and cardiac surgery [4][5][6][7][8][9]. It has been suggested that elevated ET-1 levels following ischaemia may result in the so-called ' low coronary reflow ' phenomenon [10,11].…”
Section: Introductionmentioning
confidence: 99%